Communication in Poultry Grower Relations : a Blueprint to Success. - Cole, Larry (John Wiley & Sons, 2008)
Communication in Poultry Grower Relations shows a process used to continuously improve the working relationship between integrators and their growers. A special feature is the "how to" format in which this book details the relationship process s.